Enhanced antitumor activity of combined hepatic arterial infusion chemotherapy with Lenvatinib and PD-1 inhibitors in unresectable hepatocellular carcinoma: a meta-analysis - Zhao, Lingling; Xu, Cheng; Deng, Jiewen; Ni, Yang (Frontiers in Oncology, 2025)
BackgroundHepatic arterial infusion chemotherapy (HAIC) is increasingly recognized as a primary treatment option for patients with unresectable hepatocellular carcinoma (uHCC), providing a focused treatment for localized tumors. The combination of lenvatinib, a multikinase inhibitor, with PD-1 inhibitors has demonstrated significant survival benefits in HCC. This meta-analysis aims to assess whether the integration of HAIC with lenvatinib and PD-1 inhibitors (referred to as the HAIC-L-P group) leads to better treatment effectiveness and security compared to lenvatinib and PD-1 inhibitors alone (L-P group) in uHCC.MethodsAn exhaustive search of the literature was conducted, including PubMed, the Cochrane Library, Embase, ClinicalTrials.gov, and Web of Science, from the start of each database until September 2024, to ensure a thorough and up-to-date compilation of relevant studies. Extract data on outcome measures such as overall survival (OS), progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), and adverse events (AEs). Subsequently, meta-analyses were performed using RevMan 5.4 to quantitatively evaluate the aggregated effect of the HAIC-L-P regimen versus the L-P regimen alone.ResultsIn our systematic meta-analysis of eight retrospective cohort studies, the HAIC-L-P regimen demonstrated markedly enhanced OS, with an HR of 0.54 (95% CI: 0.45-0.64; p < 0.00001), and enhanced 1-year and 2-year OS rates. Superior PFS was also observed in the HAIC-L-P group, with an HR of 0.64 (95% CI: 0.55-0.75; p < 0.0001), and higher 1-year and 2-year PFS rates. Response rates were markedly higher in the HAIC-L-P group, with an ORR risk ratio of 2.15 (95% CI: 1.84-2.50; p < 0.00001) and a DCR risk ratio of 1.28 (95% CI: 1.20-1.43; p < 0.0001). The AEs classified as grade 3 or above were elevated in the HAIC-L-P group, with notable risk ratios for vomiting, elevated AST, elevated ALT, thrombocytopenia, neutropenia, and hyperbilirubinemia. No life-threatening AEs were reported.ConclusionThe HAIC-L-P regimen correlated with enhanced tumor responses and prolonged survival, alongside manageable adverse effects, indicating its potential as a viable therapeutic strategy for individuals afflicted with uHCC.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024594109.